Intensification of Hurricane Idalia by a river plume in the eastern Gulf of Mexico - Jing Shi; Chuanmin Hu; Jennifer Cannizzaro; Brian Barnes; Yingjun Zhang; Chad Lembke; Matthieu Le Henaff (Environmental Research Letters)
Hurricane Idalia formed on 26 August 2023 and three days later rapidly intensified from a Category 1 to Category 4 strength storm in less than 24 h over the west Florida shelf. On August 30, it made landfall along Florida’s Big Bend area as a Category 3 hurricane. Strikingly, despite Idalia’s moderate intensity and favorable vortex structure, neither upper ocean thermal energy nor environmental vertical wind shear conditions were as favorable during its intensification from Category 2 to Category 4 as earlier in its path, raising the question of what external factors contributed to its extreme intensification during this phase. Using satellite data, underwater glider observations, and numerical model outputs, this study reveals that, in addition to the 2023 marine heatwave, an extensive riverine plume in the eastern Gulf of Mexico, extending from the Mississippi-Alabama-Florida shelf to the Straits of Florida, produced a ∼20 m thick low-salinity layer (∼34–34.5 psu) and a corresponding warm upper ocean (>29 °C, ∼25–30 m thick). This defined a 10–20 m thick strongly stratified barrier layer below the surface layer with buoyancy frequencies exceeding 10 ^−3 s ^−1 that suppresses vertical mixing and became a critical factor contributing to Idalia’s rapid intensification under the relatively less than favorable thermal and wind field environments. Therefore, incorporating the river plume in future forecast models appears to be essential to improve the accuracy of intensity predictions, especially in the areas affected by the plume, where stratification plays an important role in the intensification dynamics.